Psychosocial factors affecting the adoption of technology in an institution of higher education - Van Niekerk, Kirstin; Maree, David (University of the Free State, 2004)
This study investigated the psychological and social factors pertinent to the adoption of information and communication technology within a tertiary education institution. A conceptual model grouped the independent variables as individual characteristics, the individual’s perception of group characteristics and the individual’s perception of organisation characteristics. The dependent variable, the adoption of new technology, was indicated by the actual usage of telematic educational technologies by postgraduate teaching staff. In this study the results showed that attitudes towards new technology and management support were among the most important determinants of technology adoption. Certain implications for tertiary institutions were pointed out

Die studie het die sielkundige en sosiale faktore ondersoek wat belangrik is vir die aanvaarding van inligting- en kommunikasietegnologie aan ’n tersiêre onderwysinstelling. Aan die hand van ’n konseptuele model is die onafhanklike veranderlikes gegroepeer in individuele eienskappe, die individu se persepsie van groepseienskappe en die individu se persepsie van organisasie-eienskappe. Die aanvaarding van tegnologie, as die afhanklike veranderlike, was aangedui deur die mate van werklike gebruik van telematiese tegnologie deur nagraadse dosente. Die resultate in hierdie studie het aangedui dat houdings teenoor nuwe tegnologie en bestuursondersteuning van die belangrikste voorspellers is vir die aanvaarding van tegnologie. Sekere implikasies vir tersiêre onderwysinstellings word aangedui.
Keywords: Technological development; Telematic educational technologies; Technology adoption; Tertiary institutions; Higher education